Social Entrepreneurship Education and Students’ Social Entrepreneurial Intentions: The Mediating Role of Self-Efficacy in Mongolia - Altanchimeg Zanabazar; Altanchimeg Dugersuren; Tungalag Jargalsaikhan (Jurnal Ilmiah Peuradeun, 2026)
Social entrepreneurship education has increasingly been promoted as a strategic approach to addressing social and economic challenges, particularly in developing-country contexts. However, empirical evidence explaining how such education translates into students’ intentions to engage in social entrepreneurship remains limited in the Global South. This study examined the relationship between social entrepreneurship education and social entrepreneurial intention, with entrepreneurial self-efficacy serving as a mediating variable. Using a quantitative cross-sectional design, data were collected from 397 undergraduate students enrolled in five national universities in Mongolia. The data were analyzed using covariance-based structural equation modeling (CB-SEM) to test the proposed relationships. The results indicated that social entrepreneurship education had a positive but relatively modest direct effect on social entrepreneurial intention, while entrepreneurial self-efficacy showed a strong and significant influence on intention. Moreover, entrepreneurial self-efficacy partially mediated the relationship between social entrepreneurship education and social entrepreneurial intention, suggesting that education primarily shaped intention by strengthening students’ confidence in their entrepreneurial capabilities. These findings highlighted the importance of psychological empowerment in transforming educational exposure into entrepreneurial motivation. This study contributes to the social entrepreneurship literature by providing empirical evidence from an underexplored Global South context and offers practical implications for higher education institutions seeking to design more effective social entrepreneurship education programs.